Socio-cultural aspects of innovations and innovational activity (Journal of Philosophy Culture and Political Science, 2015)
The article is devoted to social-philosophical and cultural-philosophicalanalysis of the phenomenon of innovation and innovative activities.Article considers questions and problems of development of innovationsand innovative activity in modern society, regularity and forms of improvement,development of the most important spheres of innovative activity,and also some criteria and characteristics of innovations. Authors of thearticle draw a conclusion about need of research social and cultural determinantsof innovations, about system nature of innovative activity andpolicy of its meanings, and modernizations of all spheres of human activityand dynamic development of the Republic of Kazakhstan.
Keywords: society; culture; innovation; innovative activity; science; innovative economy; technopark; education; university; modernisation.